2013
DOI: 10.1038/mp.2013.155
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic microglial alterations underlie stress-induced depressive-like behavior and suppressed neurogenesis

Abstract: The limited success in understanding the pathophysiology of major depression may result from excessive focus on the dysfunctioning of neurons, as compared with other types of brain cells. Therefore, we examined the role of dynamic alterations in microglia activation status in the development of chronic unpredictable stress (CUS)-induced depressive-like condition in rodents. We report that following an initial period (2-3 days) of stress-induced microglial proliferation and activation, some microglia underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
468
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 568 publications
(504 citation statements)
references
References 87 publications
30
468
3
3
Order By: Relevance
“…In addition, recent data suggest that microglia may exhibit dynamic alterations over time as a function of duration of illness. For example, in a recent study in laboratory animals exposed to chronic unpredictable stress, microglia were found to be activated within days following stressor exposure, whereas at the end of 5 weeks of stress, microglial numbers were decreased (Kreisel et al, 2014). Depressive-like behavior was associated with both of these microglial changes, and additional data indicated that inhibiting microglia had therapeutic efficacy early in disease, whereas stimulating microglia had antidepressant effects after prolonged stress (Kreisel et al, 2014).…”
Section: Foundations For the Hypothesis That The Immune System Plays mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent data suggest that microglia may exhibit dynamic alterations over time as a function of duration of illness. For example, in a recent study in laboratory animals exposed to chronic unpredictable stress, microglia were found to be activated within days following stressor exposure, whereas at the end of 5 weeks of stress, microglial numbers were decreased (Kreisel et al, 2014). Depressive-like behavior was associated with both of these microglial changes, and additional data indicated that inhibiting microglia had therapeutic efficacy early in disease, whereas stimulating microglia had antidepressant effects after prolonged stress (Kreisel et al, 2014).…”
Section: Foundations For the Hypothesis That The Immune System Plays mentioning
confidence: 99%
“…There has been increasing interest in the use of various pharmacologic agents that can reduce microglial activation in the CNS. Drugs such as minocycline, a broadspectrum tetracycline antibiotic that effectively crosses the BBB, have been shown to have potent anti-inflammatory and neuroprotective effects in laboratory animal models of neurodegenerative disorders as well as following stress or LPS (Henry et al, 2008;Kreisel et al, 2014). Unfortunately, unlike the biologic agents that target peripheral inflammatory responses (where target engagement can be established in the periphery), microglial activation has proven difficult to assess in humans, even with currently available secondgeneration TSPO ligands, the exception being following administration of endotoxin (see above).…”
Section: Treatment In Translationmentioning
confidence: 99%
“…In recent years, there has been growing interest in the potential role of microglia in normal brain development and maturation, especially in those events that relate to synaptic pruning (Bilimoria and Stevens, 2015;Kreisel et al, 2014;Paolicelli et al, 2011;Schafer et al, 2012;Schafer and Stevens, 2013). Microglia are the major immunocompetent cells residing in the brain parenchyma and can adopt different morphological characteristics and functions: In their ramified state, they constantly survey the brain 4 microenvironment to detect and to respond to alterations in brain homeostasis, which in turn can induce the transition of ramified into phagocytic microglia (Gomez--Nicola and Perry, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As phagocytes, they can quickly remove cellular debris and dying neurons, thereby preventing possible toxic damage to neighboring cells. The phagocytic capacity of microglia is particularly important during early brain development and subsequent maturation, where they can contribute to the removal of excessive synapses in certain neuronal pathways (Bilimoria and Stevens, 2015;Kreisel et al, 2014;Paolicelli et al, 2011;Schafer et al, 2012). For these reasons, it has been suggested that abnormal microglia functions during critical periods of brain development and maturation may be an important etiopathological mechanism linking neuroinflammation to synaptic deficits (Rao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation